2003
DOI: 10.1038/sj.npp.1300284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cocaine in Rats Exposed to Heroin

Abstract: We investigated whether chronic exposure to heroin alters responses to cocaine in ways that might explain the use of cocaine by opioid addicts. To this end, the effects of cocaine (5 and 20 mg/kg) were assessed on locomotor activity of rats chronically exposed to heroin (0.0, 3.5, 7.0, and 14.0 mg/kg/day, over 14 days, via osmotic mini-pumps), or withdrawn from heroin (1 day, acute withdrawal, and 14 days, protracted withdrawal). Chronic heroin exposure, in itself, dose dependently increased locomotion and acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 101 publications
4
33
1
Order By: Relevance
“…pulse activity during morphine dependence. These data are consistent with a recent microdialysis study showing that continuous exposure to heroin elevates the basal level of DA in the nucleus accumbens (Leri et al, 2003). Notably, this change in tonic activity of VTA DA neurons during dependence coexisted with tolerance to the phasic excitatory effect of morphine.…”
Section: Morphine Induced a Change In The Firing Pattern In Vta Da Nesupporting
confidence: 81%
See 2 more Smart Citations
“…pulse activity during morphine dependence. These data are consistent with a recent microdialysis study showing that continuous exposure to heroin elevates the basal level of DA in the nucleus accumbens (Leri et al, 2003). Notably, this change in tonic activity of VTA DA neurons during dependence coexisted with tolerance to the phasic excitatory effect of morphine.…”
Section: Morphine Induced a Change In The Firing Pattern In Vta Da Nesupporting
confidence: 81%
“…These data are consistent with a recent microdialysis study showing that during acute withdrawal, basal extracellular DA levels in the nucleus accumbens were not different from those in vehicle-treated rats (Leri et al, 2003). Our data, however, contrast with the results of Diana et al (1999), who found a lasting reduction in VTA DA activity after morphine withdrawal and an augmented magnitude of the response of these neurons to morphine after 14 d of withdrawal.…”
Section: Morphine Induced a Change In The Firing Pattern In Vta Da Necontrasting
confidence: 57%
See 1 more Smart Citation
“…In our laboratory, we have examined pharmacological interactions between chronic heroin exposure (via minipump) and acute injections of cocaine (Leri et al, 2003). In both the heroin study and the present study with methadone, we have consistently observed that chronic exposure to opiate drugs elevates locomotor activity in a dose-dependent manner and that the stimulatory effects of cocaine summate with those of the opiate drugs.…”
Section: Discussionmentioning
confidence: 83%
“…The dose chosen for the cocaine challenge was 5 mg/kg (i.p. ), and the decision was based on previous studies indicating that, at this dose, cocaine induces significant elevations in locomotor activity in rats chronically exposed to heroin (Leri et al, 2003).…”
Section: Drugs and Dosagesmentioning
confidence: 99%